Предмет: Математика,
автор: altmanbraun
Преобразуйте выражение 2cos^2 a-1/1-2sin^2 a - sin^2 a
Ответы
Автор ответа:
0
Ответ:
cos^2(a)
Пошаговое объяснение:
2cos^2(a) - 1/1-2sin^2(a) - sin^2(a) = 2cos^2(a) - sin^2(a) - cos^2(a)/sin^2(a) + cos^2(a) - 2sin^2(a) - sin^2(a) = cos^2(a) - sin^2(a)/cos^2(a) - sin^2(a) - sin^2(a) = 1-sin^2(a) = cos^2(a)
sin^2(a) + cos^2(a) = 1
Похожие вопросы
Предмет: Русский язык,
автор: president2024
Предмет: Українська література,
автор: Аноним
Предмет: Русский язык,
автор: princ2003
Предмет: Литература,
автор: kvkozyrev
Предмет: Алгебра,
автор: J0VEVIP